The Role of Musical Hobbies in Enhancing Children's Learning Concentration - Wulandari, Inayah; Prasetya, Rangga Cahya; Satriawan, Wira; Semadi, I Kadek; Harahap, Herpan Syafii (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Childhood is a golden period for brain development. Musical activities such as listening, singing, and playing instruments involve various sensory and motor systems and can enhance brain function. These activities stimulate different areas of the brain and are believed to support cognitive functions, including concentration during learning. This study used a literature review method. Sources were collected from academic databases such as PubMed, Google Scholar, and ProQuest. The review found that musical activities enhanced the structure and function of several brain regions. Early musical training increased grey matter connectivity in hippocampus, primary motor cortex, supplementary motor area, and broca’s area. White matter development also occurred in motor cortex, occipital lobe, arcuate fasciculus, and corpus callosum. In addition, musical engagement activated brain's reward system, particularly involving dopamine, which supported persistence and focus in learning. Musical hobbies contributed positively to improvement of children's learning concentration. This occurred through mechanisms of brain neuroplasticity that were influenced by regular engagement with musical activities. It was recommended that musical activities be introduced from an early age, especially during golden period, with selection of appropriate types of music, such as classical music that promotes calmness and supports attention.